AI-Integrated Learning in Society 5.0: Advancing Critical Thinking in English Language Education - Deni Yuliana; Ikhfi Imaniah; Noor Azlan Ahmad Zanzali; Moh. Iqbal Firdaus (Pedagogy Review, 2026)
The rapid integration of artificial intelligence (AI) in education has transformed learning environments in the era of Society 5.0, particularly in English language education, where critical thinking skills are increasingly required to support learners’ academic and digital competencies. This study investigated the relationship between AI-integrated English for Academic Purposes-Based Learning (EAPBL) and students’ critical thinking performance among English Language Learners (ELLs). The study employed a mixed-method explanatory sequential design involving 64 undergraduate students enrolled in English-related courses at Universitas Muhammadiyah Tangerang, Indonesia. Data were collected through questionnaires, performance-based assessments, AI-supported learning tasks, students’ reflective responses, and semi-structured interviews. The questionnaire measured AI engagement, AI literacy, cognitive engagement, and perceived critical thinking skills using a five-point Likert scale, while rubric-based assessments evaluated students’ written academic outputs. Quantitative data were analyzed using descriptive statistics, paired sample t-tests, multiple regression analysis, and Partial Least Squares Structural Equation Modeling (PLS-SEM). In contrast, qualitative data were analyzed through thematic analysis to support the interpretation of the quantitative findings. The findings revealed a moderate but statistically significant improvement in students’ critical thinking performance, with an overall post-test score of 46%. Among the five dimensions of critical thinking, interpretation demonstrated the highest performance, followed by argumentation, while analysis, evaluation, and synthesis remained relatively underdeveloped. The PLS-SEM analysis indicated that AI engagement significantly influenced cognitive engagement, which in turn contributed to students’ critical-thinking performance. In addition, AI literacy strengthened the relationship between cognitive engagement and critical thinking outcomes. Qualitative findings further revealed that AI-supported learning helped students organize ideas, generate initial responses, and improve learning efficiency; however, several participants demonstrated dependence on AI-generated responses, limited critical evaluation of AI outputs, and difficulty synthesizing multiple perspectives. These findings suggest that AI-supported learning can foster critical thinking when accompanied by active cognitive engagement and adequate AI literacy. The study highlights the importance of integrating digital, cognitive, and ethical AI literacy into English language education in the context of Society 5.0.Keywords: Society 5.0, Artificial Intelligence, Critical Thinking, English for Academic Purposes-Based Learning, AI Literacy